Psychiatric diagnosis, psychiatric power and psychiatric abuse. - Szasz, T (1994)
Psychiatric abuse, such as we usually associate with practices in the former Soviet Union, is related not to the misuse of psychiatric diagnoses, but to the political power intrinsic to the social role of the psychiatrist in totalitarian and democratic societies alike. Some reflections are offered on the modern, therapeutic state's proclivity to treat adults as patients rather than citizens, disjoin rights from responsibilities, and thus corrupt the language of political-philosophical discourse.